PERLINDUNGAN HUKUM TERHADAP EKSISTENSI MATA UANG DIGITAL DI INDONESIA - Erinda Damastuti; Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: The idea of generating digital or virtual money has been put up due to the rapid advancement of technology and the currents of globalization, which will undoubtedly gradually replace the current use of physical money. A recent invention, digital currency is used for transactions all over the world. One of them is the growth of cryptocurrencies as a response to issues that conflict with current payment systems. The fact that the payment system is extensively influenced by third parties, particularly companies entrusted with overseeing digital transactions and in charge of releasing payment goods, is what leads to this issue. The absence of legislation governing it as any form of legal protection for cryptocurrencies such as bitcoin explains the lack of financial stability in the digital economy. This investigation employs a normative legal research approach based on research on relevant legal literature, such as books, statutes, and laws connected to the topics provided. Virtual currency is currency whose circulation is not controlled by a central bank and whose use is confined to those who understand it. Its use is limited to those who understand it. In Indonesia, using cryptocurrencies such as Bitcoin as a method of payment is banned. Investing in Bitcoin, on the other hand, is not merely acceptable but also lawful under Article 1320 of the Civil Code Agreement. Because so many individuals in Indonesia utilize virtual currency, it is evident that the government must create legislation severely regulating virtual currency investment in order to provide legal protection to those who invest in virtual currency. This will allow consumers who invest in virtual currencies to feel safe, secure, and at ease with their selections.Keywords : Digital Currency; Cryptocurrencies; Legal protection